Nutritional assessment and dietary intervention among survivors of childhood cancer: current landscape and a look to the future - Feit, Talia; Beals, Elizabeth; Dandekar, Smita; Kadan-Lottick, Nina; Joffe, Lenat (Frontiers in Nutrition, 2024)
Over 85% of childhood cancer patients become long-term survivors. Still, cancer and its therapies are associated with a myriad of long-term complications such that childhood cancer survivors (CCS) endure excess disease burden, morbidity, and mortality throughout their lifetimes. Existing literature suggests that CCS maintain poor dietary intake and nutritional status. Thus, as childhood cancer cure rates continue to improve, the role of diet and nutrition in mitigating many of the most common adverse long-term health outcomes among CCS has gained significant interest. Herein we present an in-depth review of existing scientific literature evaluating dietary intake and nutrition status among CCS and its impact on treatment-related health complications; as well as contemporary intervention strategies aimed at overcoming distinctive barriers and improving deleterious lifestyle behaviors in this heterogeneous, at-risk population. Patient-specific, clinical, and systemic factors act as barriers to the timely conduct of comprehensive dietary/nutritional assessments and provision of tailored, risk-based recommendations. This Mini Review discusses the current state of the science, persisting research gaps, and opportunities for advancement of assessment and intervention strategies to address the unique needs of CCS. Search Strategy: We searched PubMed for peer-reviewed articles with the search terms “pediatric cancer,” “pediatric malignancy,” “pediatric oncology,” “childhood cancer,” “survivorship,” “cancer late effects,” “long-term follow-up,” “body mass index,” “nutritional status,” “malnutrition,” “body weight,” “body weight changes,” “body composition,” “obesity,” “overweight “, “Mediterranean diet,” “DASH diet,” “processed foods,” “micronutrients,” “antioxidants,” “vitamin D,” “calcium,” “selenium,” “zinc,” “metabolic syndrome,” “heart disease,” “cardiovascular disease,” “cardiometabolic disease,” “hypertension,” “hyperlipidemia,” “HDL,” “LDL,” and “small dense LDL” from January 1, 1995, to July 21, 2023. We also selected relevant articles from our personal files and from reference lists of identified papers. We prioritized publications after 2013; however, commonly cited and highly regarded (defined by high citation count and journal impact factor) older publications were also included. Randomized controlled trials, observational studies, retrospective studies, meta-analysis, editorials, and review articles were included, whereas conference abstracts and case reports were excluded. We only searched for articles published in English, or those translated into English.